The Oil Resplendence: Evolution of the Oil Extraction Areas in Ecuador through the Night Luminosity - Mejia, Veronica (Revista de Urbanismo, 2024)
This article assesses a frequently overlooked impact, namely, the artificial illumination emanating from infrastructures associated with oil extraction installations from 2012 to 2019 located in the Amazon region, one of the places with the greatest biodiversity in the world. The primary dataset utilized in this study is derived from VIIRS nighttime satellite imagery. The significance of this research lies not only in examining light pollution but also in presenting a method for utilizing these images. The analysis focuses on Ecuador, one of the principal oil-producing nations in Latin America. The findings suggest a discernible correlation between the evolution of luminosity and the volume of crude oil production, although the luminosity shows a much higher growth rate than crude oil production. Additionally, it is observed that the elevated radiance levels in oil-rich areas yield luminous impacts comparable to those generated by major Ecuadorian cities. Consequently, this study's approach contributes to elucidating the territorial repercussions of the evolving patterns in oil consumption in a non-artificialized territory with high biodiversity. The results obtained herein aspire to instigate discourse on the environmental conditions engendered by extractive activities in their respective habitats. Furthermore, this study seeks to underscore the potential inherent in the selected data source and methodology.